Предмет: Математика,
автор: МиМииимМи
5/(x-1) – 3/(x+1) = 4(x2 – 1)
решите
Ответы
Автор ответа:
0
5/(x-1) - 3/(x+1) = 4(x2 - 1)
ОДЗ: x≠0
(x2 - 1) = (x-1)(x+1) ⇒ 5/(x-1) - 3/(x+1) = 4(x-1)(x+1) | (x+1)(x-1) - общий знаменатель ⇒ 5(x+1) - 3(x-1) = 4
5x+1-3x+3=4
5x+1-3x+3-4=0
2x=0
x=0
Ф
ОДЗ: x≠0
(x2 - 1) = (x-1)(x+1) ⇒ 5/(x-1) - 3/(x+1) = 4(x-1)(x+1) | (x+1)(x-1) - общий знаменатель ⇒ 5(x+1) - 3(x-1) = 4
5x+1-3x+3=4
5x+1-3x+3-4=0
2x=0
x=0
Ф
Похожие вопросы
Предмет: Русский язык,
автор: alimkhannursultan1
Предмет: Математика,
автор: Аноним
Предмет: Русский язык,
автор: polyna200865
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним